Respuesta del cultivo de lechuga crespa (Lactuca sativa) a la aplicación de tres láminas de riego deficitario en las terrazas de formación lenta en el campus Salache, cantón Latacunga, provincia Cotopaxi 2022. - Chisaguano Quishpe, Erick Gaspar (2022)
Increasing water scarcity has reduced water availability in the equatorial Andean zone. The purpose of this research study was to evaluate the response of the lettuce crop (Lactuca sativa) to the application of three deficit irrigation layers on the slow-forming terraces of the Salache campus, Latacunga canton, Cotopaxi province, carried out during the period April - August 2022. The treatments consisted of applying one sheet at 100% of crop evapotranspiration (control) and two deficit sheets; at 80% and 60% of crop evapotranspiration (ETc), under high-frequency localized irrigation in the lettuce,’crespa’ variety. The experimental design was a randomized complete block design with three replications. The results showed that the vegetative phase and yield of the crop were affected by water deficit (p ≤ 0,05), but there were no significant differences in the percentage of crop yield (p ≤ 0,05). It can be concluded that there is a direct proportionality between soil moisture content and the total yield obtained; thus, at 100% evapotranspiration of the lettuce crop, the yield was higher, going from 63.99 Tm/ha to 31.99 Tm/ha when 40% of its water requirement was reduced. However, irrigation at 100% Etc is the most efficient in the use of water, since 1 m3 of water allows the production of 64.76 kg of ’crespa’ lettuce. Finally, it was concluded that the cost-benefit analysis showed that the treatment at (100% ETc) is the one in with the greatest benefits and the treatment at (60% of ETc) does not provide economic benefits. The use of high-frequency drip irrigation constitutes a sustainable measure for optimizing irrigation management in situations of water scarcity or, at the same time, it could increase crop areas without increasing the availability of irrigation water.